THE ROLE OF MICRO, SMALL, AND MEDIUM ENTERPRISES (MSMEs) IN ABSORBING MANPOWER IN CIAMIS DISTRICT - Rifqi Arief Aminullah; Sariyanti Sariyanti; Husna Lailatul Qadar (Syari'ah Economics, 2020)
Since the economic crisis that occurred in Indonesia in 1997, many large-scale businesses have stagnated and even stopped their activities. The soaring population growth accompanied by an increase in the labor force creates a very complex problem, namely the increasing number of unemployed. This is due to the uneven distribution of development in all fields so that the availability of employment opportunities is not balanced. However, the Micro, Small and Medium Enterprises (MSME) sector was able to face the crisis. The research method used is descriptive-analytical by conducting research in the industri tahu bulat by CV. Macakal Pangan Sejahtera in Cipaku District, Ciamis Regency. The results showed (1) the absorption of labor by the industri tahu bulat CV. Macakal Pangan Sejahteral in Cipaku District, Ciamis Regency from 2019 reached 250 people, while in 2020 it was 136 people. There was a decrease in the number of employees between 2019 and 2020; and (2) the role of Micro, Small and Medium Enterprises (MSMEs) in the tofu industry CV. Macakal Pangan Sejahtera in the economy in Cipaku District can be seen from its position as a major player in economic activity, a large provider of employment, an important player in the development of local economic activities and community empowerment, the creation of new markets, and a source of innovation.